Diseño Y Construcción De Un Prototipo De Vehículo Eléctrico Autónomo Para La Recolección De Frutos De Palma Por Medio De Cables Vía (2023)
The activity of transferring the fruit of the oil palm, over the years has generated illnesses in the collaborators due to the repetitiveness, the risk of handling the different equipment used to date to try to improve the times, in addition to its little productivity causing more demand for products and continuity in the activity of transferring the bunches at different distances within the large cultivation areas